Enrichment and separation of Mycobacterium tuberculosis extracellular vesicles with a side of biosafety and biosecurity - Ryan, Joan M., author; Dobos, Karen M., advisor; Kruh-Garcia, Nicole A., advisor; Ellis, Robert P., committee member; Lark, Dan, committee member (Colorado State University. Libraries, 2022)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is one of the world's deadliest pathogens. Recently, TB fell from the leading infectious cause of death to the second leading infectious killer due to COVID-19. Sadly, efforts to control and prevent TB have been negatively impacted by the global pandemic: 2020 saw the first year-over-year rise in cases since 2005. Mtb has been evolving with humans for several millennia. It has the ability to transition among various states of activation for long-term survival in a multitude of microenvironments. The high adaptability of Mtb has made it difficult to control and prevent TB disease, even though anti-tubercular treatments and a vaccine have been available for decades. New prevention and control strategies, including diagnostics, treatments, and vaccines, are desperately needed to combat this public health crisis. Understanding the role of extracellular vesicles in Mtb physiology and the host-pathogen interaction may unlock new avenues for combatting TB. Extracellular vesicles (EVs) are released by virtually every living cell, serving numerous functions from biomolecule export to intercellular communication. Mtb generates EVs that are involved in response to environmental stress, virulence, and host immunomodulation. Mtb EVs have even shown promise as a highly antigenic vaccination component. Defining the role of Mtb EVs in both bacterial physiology and host-pathogen interactions is an attractive avenue for identifying new drug targets and interventions. Unfortunately, inconsistent and contradictory results in the literature have complicated a complete description of Mtb EV composition and functions. Highly reproducible enrichment techniques and a clear understanding of what biomolecules are Mtb EV associated versus co-enriched is required to fully investigate the biogenesis and roles of Mtb EVs. This work explores Mtb EV enrichment and separation with a focus on technical and biological reproducibility. Common EV enrichment techniques including size-exclusion chromatography, ultracentrifugation, and density gradient separation are directly compared for quality and consistency of Mtb EV preparation. This comparison reveals that the most commonly used technique is also the most strongly influenced by biological variation, shedding light on a potential cause for irreproducibility seen in previous Mtb EV literature. Quality control markers for Mtb EV purity assessment are also defined. For the first time, asymmetric flow field-flow fractionation (AF4) provides high resolution separation of Mtb EVs based on size. Proteomic exploration provides clarity of Mtb EV composition, with several proteins previously identified as EV associated cleanly separated from Mtb EV-containing AF4 fractions. Comparing AF4 with size-exclusion chromatography presents further insight into potential biases attributable to Mtb EV enrichment technique. The total proteomic variation between small and large Mtb EVs is negligible; however, differential detection of the lipoglycan lipoarabinomannan and changes in a subset of known secreted proteins suggest that Mtb EVs have potentially biologically relevant heterogeneity based on their size. This heterogeneity could be another contributing factor to inconsistencies in Mtb EV literature. Finally, this dissertation includes a presentation of biosafety and biosecurity from the graduate student perspective. With a focus on protecting researchers, the community, and the environment, biosafety and biosecurity are essential for the advancement of life sciences. Entering this profession during COVID-19 exemplifies the dynamic nature of risk assessment and mitigation. The spotlight on these areas due to COVID-19 provides a renewed opportunity for engagement with scientists and the community to promote a culture of safe and secure scientific research.
Zip file contains appendix.
Keywords: extracellular vesicle; proteomics; Mycobacterium tuberculosis; biosafety